2018
DOI: 10.11114/jets.v6i9.3353
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Prospective Chemistry Teachers’ Cognitive Structures and Misconceptions About Stereochemistry

Abstract: The purpose of this study was to investigate the cognitive structures of chemistry teacher candidates about "stereochemistry". A case study research method, one of the qualitative research patterns, was used in the study and the sample of study involved 28 prospective chemistry teachers who had taken Organic Chemistry I and II courses at Education Faculty of a middle Anatolian university. For the data collection, stereochemistry concept inventory comprising of 20 questions was used. In the analysis of data, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 26 publications
0
15
0
3
Order By: Relevance
“…A previous study on misconceptions about stereochemistry by Durmaz et al found that only 25% and 7.1% of the students correctly answered plane of symmetry related questions. 19 Comparison between the Students' Results from This Method Using Physical Models and the Conventional Method Using 2D Paper-Based Models…”
Section: Results Of This Assessment Methodsmentioning
confidence: 99%
“…A previous study on misconceptions about stereochemistry by Durmaz et al found that only 25% and 7.1% of the students correctly answered plane of symmetry related questions. 19 Comparison between the Students' Results from This Method Using Physical Models and the Conventional Method Using 2D Paper-Based Models…”
Section: Results Of This Assessment Methodsmentioning
confidence: 99%
“…Masalah atau isu yang disajikan berupa permasalahan lingkungan di lahan basah sehingga hal ini menambah originaltas dan otentisitas produk yang dikembangkan. Penyajian isu dinilai sebagai konflik kognitif agar terlatih menggunakan daya nalar, struktur kognitif, dan model mental mereka agar mereka memiliki pespektif sains yang ilmiah terhadap lingkungan alam sekitar (Barke et al, 2009;Darmiyanti et al, 2017;Durmaz, 2018;Gilbert & Treagust, 2009;Mahardika, Ridwan, & Rahmawati, 2018;Pande & Chandrasekharan, 2017;Yuanita & Ibrahim, 2015). Menurut (Budiningsih, 2009) bahwa, penyajian konflik kognitif merangsang daya berpikir siswa sehingga mereka secara bertahap akan mengkonstruk pengetahuannya dengan baik sesuai teori dan kajian ilmiah.…”
Section: Gambar 5 Cover Modul and Deskripsi Sajian Isu Modulunclassified
“…Pengadopsian konsep representasi secara tidak langsung akan mempengaruhi daya nalar siswa terhadap suatu fenomena dan atau gejala alam karena keutuhan berpikir secara ilmiah hanya bisa ditempuh jika siswa tidak hanya menelaah secara makroskopis tetapi secara partikulat dan simbolik ( Barke et al, 2009;Berkel et al, 2009;Chen, de Goes, Treagust, & Eilks, 2019;Farida, Helsy, Fitriani, & Ramdhani, 2018;Gilbert & Treagust, 2009;Treagust, Chittleborough, & Mamiala, 2003;Trivic & Milanovic, 2018). Selain itu, dampak terbesar yang mungkin diperoleh dari tindakan pengadopsian konsep pembelajaran kimia berbasis representasi adalah kadar miskonsepsi yang cukup menjamur dalam pembelajaran kimia mampu direduksi secara bertahap sehingga paradigma bahwa materi kimia merupakan materi yang sulit dipahami dihilangkan (Barke, Harsch, & Schmid, 2012;Durmaz, 2018;Gilbert & Treagust, 2009;Marson & Torres, 2011).…”
Section: Pendahuluanunclassified